Julie and the eagles - McDonald, Megan (American Girl Pub., 2007)
Julie and her best friend, Ivy, find a baby owl in Golden Gate Park--and it needs help. At a wildlife rescue center, Julie meets Shasta and Sierra, two bald eagles that will be caged for life, unless money is raised to release them back into the wild. For Earth Day, Julie thinks of a unique way to tell the public of the eagles' plight. The "Looking Back" section explores the beginning of the environmental movement.--From publisher's description.